Effects of experimental craniofacial pain on fine jaw motor control: a placebo-controlled double-blinded study - Kumar, Abhishek; Castrillon, Eduardo; Svensson, Krister G.; Baad-Hansen, Lene; Trulsson, Mats; Svensson, Peter (Experimental brain research, 2015)
The aim of the experiment was to test the hypothesis that experimental pain in the masseter muscle or temporomandibular joint (TMJ) would perturb the oral fine motor control, reflected in bigger variability of bite force values and jaw muscle activity, during repeated splitting of food morsels. Twenty healthy volunteers participated in four sessions. An intervention was made by injection of either 0.2 ml of monosodium glutamate/isotonic saline (MSG/IS) (randomized) in either the masseter or TMJ (randomized). The participants were asked to hold and split a flat-faced placebo tablet with their anterior teeth, thirty times each at baseline, during intervention and post-intervention. Pain was measured using a 0–10 visual analog scale. The force applied by the teeth to “hold” and “split” the tablet along with the corresponding electromyographic (EMG) activity of the jaw muscles and subject-based reports on perception of pain was recorded. The data analysis included a three-way analysis of variance model. The peak pain intensity was significantly higher during the painful MSG injections in the TMJ (6.1 ± 0.4) than the injections in masseter muscle (5.5 ± 0.5) ( P = 0.037). Variability of hold force was significantly smaller during the MSG injection than IS injection in the masseter ( P = 0.024). However, there was no significant effect of intervention on the variability of split force during the masseter injections ( P = 0.769) and variability of hold and split force during the TMJ injections ( P = 0.481, P = 0.545). The variability of the EMG activity of the jaw muscles did not show significant effects of intervention. Subject-based reports revealed that pain did not interfere in the ability to hold the tablet in 57.9 and 78.9 %, and the ability to split the tablet in 78.9 and 68.4 %, of the participants, respectively, during painful masseter and TMJ injections. Hence, experimental pain in the masseter muscle or TMJ did not have any robust effect in terms of bigger variability of bite force and jaw muscle activity, during repeated splitting of food morsels.